EVALUATION OF THE ECONOMIC AND BRAND ACTIVITIES OF A REGIONAL TOURISM COMPANY - Mukhitdinov, Khudoyor Suyunovich; Bozorov, Samar Safarovich (THE INNOVATION ECONOMY, 2026)
This study analyzed the level of utilization of hotel industry capacities in the development of regional tourism. The results showed that some hotels have high occupancy rates, while others have insufficient use of infrastructure resources. The study identified the reasons for this imbalance and developed proposals for strengthening marketing, diversifying services, and developing digital booking systems.